Consumer Purchase Interest in Local and Imported Halal Products in the Marketplace from an Islamic Economic Perspective - Suhaila Irfi; Syarlla Lidia Putri; Reni Ria Armayani Hasibuan (CV. Era Digital Nusantara, 2026)
This study aims to analyze the purchasing interest of Gen Z Muslim consumers in local and imported halal products in marketplaces from an Islamic economic perspective. Employing a descriptive quantitative approach, data were collected via a Likert-scale questionnaire from 30 active marketplace users aged 18–22 and analyzed using descriptive statistics (frequency distribution and percentage). The results reveal a phenomenon of Halal Certification Primacy, where official halal certification and clear halal information act as the primary determinants of purchasing decisions (86.7%). Furthermore, 86.7% of respondents showed high interest in local halal products, with 93.3% believing local quality can compete with imports. Meanwhile, 90% remained open to imported products provided halal assurance is met. Notably, 96.7% of respondents integrate Islamic economic principles, specifically mashlahah (benefit) and tayyib (goodness), into their consumption decisions. The scientific contribution of this study lies in enriching the literature on digital consumer behavior by integrating Islamic economic principles into the mapping of halal product preferences across origins (local vs. imported), providing empirical evidence that modern Muslim consumption is driven by a blend of spiritual commitment and economic rationality.